SINTESIS SILIKA MESOPORI DENGAN GELATIN TULANG SAPI SEBAGAI CETAKAN MENGGUNAKAN METODE HIDROTERMAL DAN SONOKIMIA SERTA UJI KAPASITAS ADSORPSINYA TERHADAP METILEN BIRU - , PRISKA M. PATTIASINA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The utilization of bovine bone gelatin as a template for the synthesis of mesoporous silica using hydrothermal and sonochemical methods, as well as its adsorption capacity test to methylene blue, have been studied. Bovine bone gelatin which is selected as the template is gelatin that obtained from pretreatment with NaOH, citric acid, and HCl for 24 hours and followed by hydrolysis at 80 Â°C. Gelatin from this variation has the distribution value of molecular weight around 120-160 kD. The value of molecular weight distribution indicates that the gelatin result is constituted by Î± chains. The synthesis of mesoporous silica was conducted with two methods, i.e. hydrothermal and sonochemical methods. The syntheses of these two methods were capable of producing mesoporous silica with meso scale pore diameter. Both of the syntheses mesoporous silica result can be applied as absorbent to methylene blue adsorption. Mesoporous silica with hydrothermal method has a pore diameter size of 5.14 nm, and adsorption capacity of methylen blue by 0.09 mmol/g. Mesoporous silica with sonochemical method has a pore diameter size of 3.13 nm, and adsorption capacity of methylene blue by 0.08 mmol/g. The adsorption capacity of mesoporous, which is synthesized by the sonochemical method, was able to match the adsorption capacity of silica mesoporous by hydrothermal method synthesis.